Biogenic calcareous growth on the ribbed mussel Aulacomya atra (Bivalvia: Mytilidae) favours polydorid boring (Polychaeta: Spionidae) - Diez, María Emilia (2015)
Shells of the ribbed mussel Aulacomya atra from the Patagonian gulfs of San Matı´as and San Jose´ (Argentina) are commonly bored by polydorids and covered by serpulids and crustose coralline algae. As the co-occurring mussel Mytilus edulis is neither bored by polydorids nor covered by coralline algae, we hypothesize that early or previous calcareous growth would favour larval settlement and boring by polydorids. Generalized Linear Model analyses showed that polydorid boring is indeed positively correlated with the abundance of serpulids and crustose coralline alga. Infestation by polydorids is higher in larger, older ribbed mussels due to their correspondingly higher available area for larval settlement. Increasing polydorid infestation adversely affects the condition index of A. atra.